PERSEPSI WAJIB PAJAK ORANG PRIBADI DI JAKARTA TERHADAP PENGGELAPAN PAJAK (TAX EVASION) - Celine Meidita, Ngadiman (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
The success of self-assessment system is voluntary compliance with the tax laws. The purposes of this study are to examine the relationship between tax knowledge, tax fairness, law enforcement level towards tax evasion behavior of registered individual taxpayers in KPP DKI Jakarta. Type of this research is quantitative research by using primary data. Sampling was done using purposive sampling with 90 individual taxpayers respondent in Jakarta. The result of double regression test shows that the impact of tax knowledge, tax fairness, and law enforcement level simultaneously affect to the tax evasion behavior. Three independent variables affect the dependent variable is 34,1%, which means 34,1% variation from tax evasion explained by tax knowledge, tax fairness, and law enforcement level.